Rancang Bangun Sistem Keamanan Kandang Sapi Perah Dengan Arduino Berbasis Android - Rusito; Muhammad Naufal Ra’if (Elkom : Jurnal Elektronika dan Komputer, 2024)
Most dairy farmers in our country still rely on human labor to monitor the condition of their farm areas. The current problem is the manual security system for barns, meaning that the barns need to be constantly checked around the area at all times. This is especially risky at night, when livestock theft is more likely to occur. This research implements PIR sensor technology to monitor movements around the barn, MC-38 magnetic sensors for gate security, and utilizes Android smartphones as devices to display barn data processing results, allowing real-time monitoring of barn security. The research is conducted using the Research and Development (R&D) method by Borg & Gall, encompassing only six steps. The results of the system evaluation by experts show a score of 3, falling between 2.1 – 3.0, categorized as Valid. User validation results show a score of 27.2, also falling between 2.1 – 3.0, categorized as Effective.